Phobia of the Supernatural: A Distinct but Poorly Recognized Specific Phobia With an Adverse Impact on Daily Living - de Oliveira-Souza, Ricardo (Frontiers in Psychiatry, 2018)
The psychological and psychiatric literature has seldom appreciated that fears of ghosts and kindred supernatural worries may be a cause of intense discomfort, poor sleep, and socio-occupational impairment. This claim is illustrated by the clinical features of six patients who developed intense anxiety when they had to sleep alone at night. The fears were first noticed in childhood and persisted into adolescence and adulthood. At these times, they were overwhelmed by images of ghosts and haunted houses often experiencing a vivid impression that an immaterial being not perceivable by the ordinary senses was hovering around. Comorbidity with other phobias was the rule-. Owing to shame and self-consciousness, the fears were seldom if ever discussed with healthcare professionals. The overall clinical and psychopathological picture was consistent with a diagnosis of a specific phobia. In at least a few cases, response to pharmacological treatment and cognitive-behavioral intervention has alleviated the symptoms. “Phobia of the supernatural” may be more common than usually thought. It must actively be sought for in patients complaining of poor sleep and daytime somnolence, and in patients with other types of phobia. Systematic studies must be carried out to settle the neurobiological correlates of phobia of the supernatural as well as the possible benefit of different modalities of pharmacological and psychological treatment.